Penerapan Model Pembelajaran Means Ends-Analisys (MEA) Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMA - Satjun Siregar; Mumun Syaban; Irmawan (EDUCARE, 2017)
This study aims to determine the improvement of mathematical problem solving abilities of high school students. Students' mathematical problem solving ability is one of the abilities that must be possessed by each student. In fact, mathematical problem solving skills have not received much attention from teachers. Another disadvantage is the lack of non-routine problems given by the teacher to be solved by students. Another problem is the learning model that applies the Lecture Method, Questions and Answers and assignments to students who are more dominant so that it does not encourage student activity and participation in resolving mathematical problem solving problems. Improving mathematical problem solving skills, students need to be encouraged to be able to solve non-routine questions. to solve problem solving problems mathematically, the teacher needs to prepare the right learning model. Learning is needed that integrates knowledge so that students are able to find solutions, skills to solve problems, creative thinking, emphasize the experience and involvement of students actively in problem solving. One of the learning models that can be done is applying the Means Ends Analysis (MEA) learning model.